Understanding the Usage of Whatsapp Among Malaysian Employees Through the Lens of Social Influence Theory - Su Mustaffa, Che; Hasniza Che Soh, Che; Abu Bakar, Hassan; Mohamad, Bahtiar (International Journal of Engineering and Technology, 2018)
The study examines the social influence factors that affect the intention for using WhatsApp application among employees in a Malaysian organisation. The objectives of the study are to ascertain the reasons for the employees to currently use WhatsApp and to examine the factors that affect the use of WhatsApp based on Social Influence Theory perspective. The nature of the study’s methodological design was qualitative. The main instruments for data collection were focus group discussions and in-depth interviews. Purposive sampling technique was adopted to ensure that the employees chosen had the relevant knowledge about WhatsApp. The findings indicated that compliance, internalization and identification were three important social factors that could influence the employees to use WhatsApp in their routine work as predicted by Social Influence Theory. This study contributes some insights regarding the factors that can contribute to the usage of social media and strengthen the ideas of Social Influence Theory in Malaysian context.